Fabrication and optimization calix[8]arene-PbS nanoadsorbents for the adsorption of methylene blue: isotherms, kinetics and thermodynamics studies - Rosly, Nor Zida; Ishak, Syahirah; Abdullah, Abdul Halim; Ahmad Kamarudin, Mazliana; Ashari, Siti Efliza; Alang Ahmad, Shahrul Ainliah (Elsevier, 2022)
The present study aims to determine the adsorption behaviour of methylene blue (MB) dye based on calix[8]arene-modified lead sulphide (PbS) nanoadsorbents under optimal conditions. Response surface methodology (RSM) was executed to evaluate the interactive effect of three factors (adsorbent dosage, contact time, and pH) on the adsorption of MB dye using a central composite design (CCD). The optimised values for adsorbent dosage, contact time, and pH solution were found to be 45.00 mg of calix[8]arene-modified PbS, contact time of 180 min, and pH 6. This study reports the results of batch adsorption experiments, which include the adsorption capacity, kinetics, and isotherm of the MB adsorption process. Pseudo-first order and pseudo-second order were demonstrated for their quality to fit the data. Pseudo-second order was the best in fitting the adsorption data with the higher R2 values (R2 > 0.928), indicating chemisorption to be the mechanism of adsorption. The Langmuir and Freundlich equilibrium models were employed to determine the isotherm parameters. The equilibrium assessment illustrated that the Langmuir isotherm model fitted well with the adsorption data, and a maximum MB adsorption capacity of 11.90 mg/g was achieved. The characterisation studies with EDX, FESEM, and FTIR indicated a successful synthesis of calix[8]arene-modified PbS.